الاستراتيجية الزراعية لوزارة الزراعة بالولاية الشمالية ودورها في توفير العمالة وتطويرها بمصانع الصناعات الغذائية بالولاية الشمالية - السودان - أحمد، عبدالكريم عبدالرحمن محمد (جامعة دنقلا - كلية الدراسات العليا, 2023)
هدفت الدراسة إلى التعرف على الاستراتيجية الزراعية بوزارة الزراعة بالولاية الشمالية ودورها في توفير فرص عمل العمالة بمصانع الصناعات الغذائية بالولاية الشمالية وتطويرها، ولتحقيق هذا الهدف تم جمع البيانات والمعلومات من خلال استبانة صممت لهذه الغاية، حيث أجريت الدراسة الميدانية للتعرف على وجهات نظر بعض العاملين بمصانع الصناعات الغذائية بالولاية الشمالية وعددهم (40) مبحوثاً. تم استخدام المنهج الوصفي التحليلي في الدراسة، ومن ثم تمت معالجة البيانات إحصائياً باستخدام برنامج الحزم الإحصائية للعلوم الاجتماعية (SPSS)، وتبيان العلاقات عن طريق نموذج الانحدار. توصلت الدراسة إلى عدة نتائج أهمها: وجود علاقة ذات دلالة إحصائية بين استراتيجية للإنتاج الزراعي بالولاية الشمالية وتوفير العمالة وتطويرها بمصانع الصناعات الغذائية بالولاية الشمالية. وقد خرجت الدراسة بعدة توصيات أهمها: ضرورة مساهمة الاستراتيجية الزراعية في توفير فرص العمالة من خلال قيام مصانع للصناعات الغذائية بالولاية واستيعاب العدد المأمول من العمالة والاهتمام بتدريبها وتطوير قدراتها، وإيجاد مزيد من التنسيق بين إدارات مصانع الصناعات الغذائية وإدارات وزارة الزراعة بالولاية الشمالية. The study aims to identify the agricultural strategy, and its role in providing work opportunities together with developing employment at food industry factories in the Northern State, To achieve the above mentioned aim, the data and information were collected via a questionnaire specially designed for this purpose. The field study was conducted to identify the viewpoints of some employees at the food industry factories in the Northern State whose numbers were 40 respondents. The descriptive analytical method was employed to process the data statistically using the programme of Statistical Packages for Social Sciences (SPSS), and the relationships were explained through Chi square and regression model. The study has arrived at a number of findings of the most important were the existence of a relationship of statistical indication between agricultural production strategy in the Northern State, and the availability of employment development at food industry factories in the Northern State. The study has concluded with some important recommendations including the contribution in providing work opportunities through setting up food industry factories at the Northern State to absorb a considerable number of employees together the appropriate training to raise their capabilities and finding more coordination between the management at the food industry factories and management of the ministry of agriculture in the Northern State.
Keywords: الموارد الطبيعية -- التخطيط الاستراتيجي -- القطاع الزراعي -- الصناعات الغذائية -- السودان